The Politics and Institutions of global Energy Governance - Graaf, Thijs Van de. author. aut Link
XVI, 206 p.
Keywords: From climate change over shale gas to the race for the Arctic, energy makes headlines in international politics almost daily. Thijs Van de Graaf argues that energy is in dire need of global governance. He traces the history of international energy cooperation from the notorious 'Seven Sisters' oil-companies cartel to the recent creation of the International Renewable Energy Agency (IRENA). He analyses how international institutions have been created for securing oil rents, coordinating consumer-countries' energy security policies, promoting producer-consumer dialogue, managing regional gas markets, and dealing with energy-related environmental externalities. Drawing on the emerging regime complexity literature, he constructs a novel analytical framework to explain the fragmented architecture of global energy governance, and studies prospects for institutional reform at the International Energy Agency (IEA) and the G8/G20.